Protease activated-receptor 2 is necessary for neutrophil chemorepulsion induced by trypsin, tryptase, or dipeptidyl peptidase IV. Issue 1 (11th December 2017) - White, Michael J V; Chinea, Luis E; Pilling, Darrell; Gomer, Richard H
Abstract: Compared to neutrophil chemoattractants, relatively little is known about the mechanism neutrophils use to respond to chemorepellents. We previously found that the soluble extracellular protein dipeptidyl peptidase IV (DPPIV) is a neutrophil chemorepellent. In this report, we show that an inhibitor of the protease activated receptor 2 (PAR2) blocks DPPIV-induced human neutrophil chemorepulsion, and that PAR2 agonists such as trypsin, tryptase, 2f-LIGRL, SLIGKV, and AC55541 induce human neutrophil chemorepulsion. Several PAR2 agonists in turn block the ability of the chemoattractant fMLP to attract neutrophils. Compared to neutrophils from male and female C57BL/6 mice, neutrophils from male and female mice lacking PAR2 are insensitive to the chemorepulsive effects of DPPIV or PAR2 agonists. Acute respiratory distress syndrome (ARDS) involves an insult-mediated influx of neutrophils into the lungs. In a mouse model of ARDS, aspiration of PAR2 agonists starting 24 h after an insult reduce neutrophil numbers in the bronchoalveolar lavage (BAL) fluid, as well as the post-BAL lung tissue. Together, these results indicate that the PAR2 receptor mediates DPPIV-induced chemorepulsion, and that PAR2 agonists might be useful to induce neutrophil chemorepulsion.